The application of tripod polishing and focused ion beam milling to the TEM specimen preparation of HVOF thermally sprayed coatings - Kong, Gaoning; McCartney, D. Graham; Brown, Paul D. (Institute of Physics Publishing, 2004)
The microstructure of high velocity oxy fuel thermally sprayed coatings is highly anisotropic and inhomogeneous. Tripod polishing has enabled the preparation of samples with up to 0.5mm diameter electron transparent areas, where a statistically significant number of features could be examined. Conversely, FIB has been used to prepare TEM samples for site-specific analysis of sub-micron regions of interest, e.g. for the interface characterisation between metallic coatings and the substrate, or the study of secondary precipitation on pre-existing phases in cermet coatings.